Seasonal variations of sea–air CO2 fluxes in the largest tropical marginal sea (South China Sea) based on multiple-year underway measurements - W.-D. Zhai; M.-H. Dai; B.-S. Chen; X.-H. Guo; Q. Li; S.-L. Shang; C.-Y. Zhang; W.-J. Cai; D.-X. Wang (Biogeosciences, 2013)
Based upon 14 field surveys conducted between 2003 and 2008, we showed that the seasonal pattern of sea surface partial pressure of CO2 (pCO2) and sea–air CO2 fluxes differed among four different physical–biogeochemical domains in the South China Sea (SCS) proper. The four domains were located between 7 and 23° N and 110 and 121° E, covering a surface area of 1344 × 103 km2 and accounting for ~ 54% of the SCS proper. In the area off the Pearl River estuary, relatively low pCO2 values of 320 to 390 μatm were observed in all four seasons and both the biological productivity and CO2 uptake were enhanced in summer in the Pearl River plume waters. In the northern SCS slope/basin area, a typical seasonal cycle of relatively high pCO2 in the warm seasons and relatively low pCO2 in the cold seasons was revealed. In the central/southern SCS area, moderately high sea surface pCO2 values of 360 to 425 μatm were observed throughout the year. In the area west of the Luzon Strait, a major exchange pathway between the SCS and the Pacific Ocean, pCO2 was particularly dynamic in winter, when northeast monsoon induced upwelling events and strong outgassing of CO2. These episodic events might have dominated the annual sea–air CO2 flux in this particular area. The estimate of annual sea–air CO2 fluxes showed that most areas of the SCS proper served as weak to moderate sources of the atmospheric CO2, with sea–air CO2 flux values of 0.46 ± 0.43 mol m−2 yr−1 in the northern SCS slope/basin, 1.37 ± 0.55 mol m−2 yr−1 in the central/southern SCS, and 1.21 ± 1.48 mol m−2 yr−1 in the area west of the Luzon Strait. However, the annual sea–air CO2 exchange was nearly in equilibrium (−0.44 ± 0.65 mol m−2 yr−1) in the area off the Pearl River estuary. Overall the four domains contributed (18 ± 10) × 1012 g C yr−1 to the atmospheric CO2.